Droplet coalescence and clustering behavior in microsphere-filled polymeric emulsions under shear flow: the key role of asymmetric interfacial affinities. Issue 6 (21st January 2016) - Mao, Chaoying; Kong, Miqiu; Yang, Qi; Li, Guangxian; Huang, Yajiang
Abstract : The asymmetric affinities of interfacially located microspheres lead to diverse flow-induced spatial arrangements of droplets in viscous polymeric emulsions with different compositions. Abstract : The flow-induced spatial organization of the droplet phase in ternary polymeric emulsions consisting of two Newtonian fluids, namely polyisobutylene (PIB) and polydimethylsiloxane (PDMS), in the presence of a small amount of solid polystyrene (PS) microspheres are explored by direct flow visualization. The results suggest that the asymmetric affinities of interfacially located PS microspheres to two fluid components lead to diverse flow-induced morphologies in PIB/PDMS blends with different compositions. In 10/90 blends where microspheres are preferentially wetted by the PIB droplets, significantly promoted coalescence of PIB droplets is observed. Increasing the loading of microspheres or changing the shear rate will alter the size and spatial distribution of PIB droplets. In contrast, in the inverse 90/10 blends where microspheres are wetted by the continuous PIB phase, bridging of PDMS droplets is found, leading to the generation of string-like or grape-like clusters. These results indicate that the flow-induced morphology of PIB/PDMS blends in the presence of PS microspheres is not only determined by the experimental conditions such as shear rate but also to a large extent by the asymmetric interfacial affinities of microspheres for fluid components.